Meningkatkan Kesadaran Finansial Digital pada Generasi Z melalui Kegiatan Sosialisasi di SMK Sunan Drajat 3 Babak Bawo Dukun - M. Nasyah Agus Saputra; Dwi Afrianti; Lailatul Fitriyah; Fatihatus Sahliyah; Narissa Febrianty; Nata Zahroh (Civiliza Publishing, 2025)
Continuous developments in digital technology have led to an increasing use of application-based financial services among Generation Z. However, this trend has not been fully accompanied by adequate financial management capabilities, resulting in a gap between technological access and financial literacy. This community service activity aims to enhance digital financial literacy among twelfth-grade students at SMK Sunan Drajat 3 Babak Bawo Dukun in order to foster rational, adaptive, and long-term financial behavior. The study employs an educative-participatory approach through the delivery of instructional materials, interactive discussions, quizzes, and experience sharing, involving university students as facilitators of contextual learning. The findings indicate that although students demonstrate a high level of familiarity with digital financial services, their understanding remains largely limited to technical aspects and has not fully encompassed conceptual dimensions such as financial planning, consumption control, and saving behavior. Post-activity evaluation reveals an improvement in students’ financial understanding and awareness. These results confirm that the educative-participatory approach is effective in bridging the gap between the use of financial technology and financial management capabilities. Overall, this activity contributes to strengthening the financial readiness of vocational high school students as part of Generation Z in facing the challenges of the digital economy and highlights the importance of developing sustainable, contextual, and experience based digital financial literacy programs.